1995
DOI: 10.1159/000284894
|View full text |Cite
|
Sign up to set email alerts
|

Correlational Studies of the Scale for the Assessment of Negative Symptoms and the Scale for the Assessment of Positive Symptoms: An Overview and Update

Abstract: The interrelationships between the various symptoms of schizophrenia may be explored by examining their intercorrelations. Five different factor analytic studies, which examine these interrelationships, are summarized. Three major factors emerge consistently: psychotic, disorganized, and negative. These three factors appear to represent three dimensions of the psychopathology of schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
0
5

Year Published

1997
1997
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 152 publications
(80 citation statements)
references
References 24 publications
3
72
0
5
Order By: Relevance
“…Somewhat in accordance with the present findings of lower frequencies in the more disordered patients, Spencer et al [14] showed that patients with high levels of hallucinations had lower frequencies of the visual evoked gamma activity. Previously, in our report with the full sample of SZS patients [4], we did not see any correlation between evoked responses and positive or negative symptoms rated with the Scales for the Assessment of Positive Symptoms (SAPS) and the Scales for the Assessment of Negative Symptoms (SANS) [15], but others have shown that a reduction of auditory gamma activity correlates with negative symptoms [16] and working memory deficits [17]. A reduction of left-hemisphere auditory evoked gamma amplitude has been specifically associated with an increased PANSS (Positive and Negative Syndrome Scale) general score [18].…”
Section: Discussionmentioning
confidence: 83%
“…Somewhat in accordance with the present findings of lower frequencies in the more disordered patients, Spencer et al [14] showed that patients with high levels of hallucinations had lower frequencies of the visual evoked gamma activity. Previously, in our report with the full sample of SZS patients [4], we did not see any correlation between evoked responses and positive or negative symptoms rated with the Scales for the Assessment of Positive Symptoms (SAPS) and the Scales for the Assessment of Negative Symptoms (SANS) [15], but others have shown that a reduction of auditory gamma activity correlates with negative symptoms [16] and working memory deficits [17]. A reduction of left-hemisphere auditory evoked gamma amplitude has been specifically associated with an increased PANSS (Positive and Negative Syndrome Scale) general score [18].…”
Section: Discussionmentioning
confidence: 83%
“…30 Psychotic symptoms were quantified using the scale for the assessment of positive symptoms and negative symptoms. 31 Similarly, healthy relatives and controls were examined by a psychiatrist. The Structured Clinical Interview SCID II 32 and a personality inventory (Freiburger Persö nlichkeitsinventar) 33 were additionally applied to detect personality traits or disorders which might influence autonomic function.…”
Section: Study Populationmentioning
confidence: 99%
“…Severity of psychopathology: The Scales for Assessment of Positive Symptoms and Negative Symptoms (SAPS and SANS, respectively) (Andreasen, Arndt, Miller, Flaum, & Nopoulos, 1995;Andreasen and Olsen, 1982) assess a total of 49 individual signs and symptoms. Individual items are grouped together to include five positive symptoms (hallucinations, delusions, positive formal thought disorder, bizarre behavior, and catatonic motor behavior) and five negative symptoms (alogia, affective blunting, avolition, anhedonia, attentional impairment) for which global ratings are designated.…”
Section: Mental Healthmentioning
confidence: 99%